Building better homes : government strategies for promoting innovation in housing - Hassell, Scott, 1974- (RAND, 2003)
This report examines the structure, characteristics, and motivations of major participants in the housing industry to explore how innovation might be accelerated. It identifies options and strategies for the federal government to consider as it attempts to further advance innovation in housing to make homes more affordable, durable, and safe. Housing is the largest component of the nation's physical wealth, representing nearly 20 percent of the nation's gross domestic product. Therefore, innovation in that industry would contribute positively to increase productivity and provide benefits t.